2017
DOI: 10.20473/mog.v24i2.4485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of percutaneous nephrostomy in late stage cervical cancer’s survival with impaired renal function

Abstract: Objective: explore the association between percutaneous nephrostomy and survival of patients with advanced cervical cancer accompanied by renal impairment.Materials and Methods: Retrospective cohort, with 70 samples taken with consecutive sampling. The population was all advanced cervical cancer patients with impaired renal function (IIIB, IVA, IVB, recurrent) treated in RSUPNCM since January 1, 1998. Sample size was each 19 patients for percutaneous nephrostomy and conservative groups. Survival was measured f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Transformasi konflik tidak terjebak kepada pemahaman konflik secara ad hoc, tetapi mencari akar konflik yang menjadi pola berkelanjutan dalam setiap konflik. Dan melalui transformasi konflik diharapkan akan menyediakan kerangka perubahan yang diinginkan ke depan, sehingga Rasjidi (1968) mengatakan agama adalah absolut, sehingga adalah hal yang sulit berbicara objektif dalam soal agama karena ia involved (terlibat). Menurutnya ia mengakui bahwa dalam kenyataan sejarah masyarakat adalah multi-complex, religious-pluralism, bermacam-macam agama.…”
Section: Islam Dan Pendidikan Cinta Damaiunclassified
“…Transformasi konflik tidak terjebak kepada pemahaman konflik secara ad hoc, tetapi mencari akar konflik yang menjadi pola berkelanjutan dalam setiap konflik. Dan melalui transformasi konflik diharapkan akan menyediakan kerangka perubahan yang diinginkan ke depan, sehingga Rasjidi (1968) mengatakan agama adalah absolut, sehingga adalah hal yang sulit berbicara objektif dalam soal agama karena ia involved (terlibat). Menurutnya ia mengakui bahwa dalam kenyataan sejarah masyarakat adalah multi-complex, religious-pluralism, bermacam-macam agama.…”
Section: Islam Dan Pendidikan Cinta Damaiunclassified
“…5 A study by Rasjidi showed a significant longer survival in patients with advanced cervical cancer who underwent percutaneous nephrostomy, even though the median survival was only 203 days. 6 Another study by Lapitan et al showed there was no evidence of an impact on quality of life and the decision to offer diversion surgery might be based solely on a survival benefit, 7 which is modest but potentially important to patients to able them continue their treatment and spent their time with their family. Various method of urinary diversion could be used for palliative urinary diversion.…”
Section: Introductionmentioning
confidence: 99%